STRATEGI KOMUNIKASI HOST LIVE PADA AKUN @RICISM_ DALAM MEMANFAATKAN FITUR LIVE TIKTOK SEBAGAI DAYA TARIK AUDIENS - Handayani, Tri Mega; Suryo, Herning; Muadz, Muadz (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
The advancement of technology has transformed how people behave, particularly in their use of social media. This research aims to understand the communication strategies employed by the live host on the TikTok account @Ricism_ as they utilize the live feature to attract and retain their audience. Live hosts play a crucial role in maintaining viewer engagement during live broadcasts. This study employs a qualitative method, collecting data through interviews and documentation. Interviews were conducted with informants who are followers of @Ricism_ and meet specific criteria. Using Laswell's theory and the SMCRE model (Source, Message, Channel, Receiver, Effect), the study reveals that TikTok serves as an effective channel for live broadcasts. The live host exhibits clear expertise and credibility, delivering messages in a way that is easy to understand and ensuring that the topics discussed remain engaging and varied. The analysis indicates that the communication strategies implemented by host @Ricism_ significantly enhance audience appeal. Their spontaneous and flexible choice of topics and engaging delivery style captivate the audience, ultimately leading to behavioral changes such as giving gifts, leaving comments, and liking the live stream features available on TikTok.